Determination of the oxidation kinetics of high loaded CuO-based materials under suitable conditions for the Ca/Cu H2 production process. (1st May 2018) - Díez-Martín, L.; Grasa, G.; Murillo, R.; Martini, M.; Gallucci, F.; van Sint Annaland, M.
Highlights: The oxidation reaction of highly-loaded CuO-based materials have been investigated under atmospheric and pressurized conditions. The intrinsic kinetic parameters have been obtained. The Shrinking Core Model kinetically controlled has been successfully applied. The pressure has not a significant effect on oxidation kinetics. Abstract: In this work, the oxidation reaction of high loaded CuO-based materials was investigated under atmospheric and pressurized conditions. The oxygen transport capacity of the materials was firstly tested in the TGA and no losses greater than 5% were observed along 100 oxidation/reduction cycles. The kinetic parameters governing the oxidation reactions of the selected CuO-based materials were determined using a shrinking core model with chemical reaction control. The experimental results suggested that a SCM with chemical reaction control is able to predict the oxidation conversion of high loaded CuO-based materials in powder and pellet form. On the other hand, the effect of total pressure on materials reactivity was analyzed. The kinetic parameters obtained under atmospheric conditions were applied to fit the experimental data obtained under pressurized conditions. The results confirmed that the pressure has not an important effect on the oxidation kinetics of high loaded CuO-based materials and the parameters obtained at atmospheric pressure can be applied to study the oxidation under pressurized conditions.